Perbandingan Penambahan CMC dan Sorbitol dengan Penambahan Gelatin dan Gliserol terhadap Edible Film yang Terbuat dari Limbah Cair Tahu - Hadistya Suryadri (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2020)
The large number of small tofu industries do not have liquid waste treatment encourage the utilization of their whey become raw of edible film because its protein content. However using only protein as a raw material of edible film resulting brittle, fragile and rigid films. Accordingly, the addition of hydrocolloids such as CMC or gelatin to repair film structure and also addition of plasticizers such as sorbitol and glycerol to improve film elasticity. The aim of this study to determine the effect of ratio concentration CMC-Sorbitol and Gelatin-Glycerol from 1% : 1%, 1% : 3%, 1% : 5%, 3% : 1%, 3% : 3%, 3%: 5%, 5% : 1%, 5% : 3% to 5% : 5% (weight/volume) on the physical properties of whey based films. Film resulted good properties in accordance with the Japan Industrial Standard at using ratio CMC-Sorbitol 1%:3% and ratio Gelatin-Glycerol 3%:3%. Appearance of film with addition of Gelatin-Glycerol 3%:3% relatively more transparent and smooth compared to film with addition of CMC-Sorbitol 1%:3%. Micrograph of CMC-Sorbitol 1%:3% film surfaces observed rough and many cracks and very irregular in structures.